From fairness to loyalty: The mediating role of complaint handling satisfaction on airline passengers repurchase intention - Mahmud, Azuati; Othman, Abdul Kadir; Sakarji, Siti Rosnita; M. Suaree, Mohamad Atheef Hannan; Omar, Siti Nur Zahirah (International Journal of Accounting, Finance and Business, 2025)
This study dives into how perceived fairness affects airline passengers' willingness to repurchase, especially looking at how satisfied they are with how their complaints are handled. It explores three key aspects of justice: procedural, distributive, and interactional, and how these factors influence satisfaction with complaint management in the Malaysian airline scene, focusing on Malaysia Airlines Berhad and AirAsia. This study used a quantitative method, sending a structured questionnaire to 500 passengers who filed complaints in 2020; 405 valid responses were received. The analysis, which included correlation and multiple regression, showed strong positive links between all dimensions of justice, satisfaction with complaint handling, and the intention to repurchase. Procedural justice was the strongest predictor of satisfaction, followed by distributive justice, while interactional justice fully mediated the effect through satisfaction. The results indicate that satisfaction with complaint handling partially mediates the relationship between procedural justice and repurchase intention and fully mediates the effect of interactional justice. Distributive justice had a minimal direct effect on repurchase intention. These findings emphasize that passengers perceive fairness in complaint resolution, primarily through fair procedures and just outcomes, and that this perception plays a crucial role in their satisfaction and loyalty. On a practical level, the study suggests that airlines can boost customer loyalty and encourage repeat business by adopting transparent, fair, and empathetic complaint handling practices. This research adds to the service management literature by shedding light on how perceptions of justice impact loyalty in the airline industry and highlights the strategic importance of effective service recovery in competitive markets.